Biodiversité méditerranéenne et changements globaux : cas du complexe de zones humides de Guerbès-Senhadja (Algérie) - Oumessaad Toubal; Abderrazak Boussehaba; Abderrahmane Toubal; Boudjéma Samraoui (Physio-Géo)
The Guerbès-Senhadja wetland complex is located in north-eastern Algeria, in water-stressed North Africa, one of the most vulnerable regions to climate change (M. HULME et al., 2001). Although identified as one of the hotspots of biodiversity, and granted a formal protection as a Ramsar site, the ecocomplexe has undergone over the last two decades, fast changes in land use that has left many of its natural habitats heavily impacted and degraded, posing a tough challenge to the sustainable use of its natural resources.As climate change will affect the hydrology of wetlands mostly through changes in precipitation and temperature regimes, we attempted first to investigate warming trend and changes in rainfall patterns in the studied area by comparing these two factors over two periods: 1923-1938 and 1987-2007. Our results are in line with some predictive climatic scenarios which expect temperatures to change in North Africa between 0.2 °C and 0.5 °C per decade (M. HULME et al., 2001).Using remote sensing, we drew up a map of land use and vegetation cover across the studied area as a first step to establish the status of the various ecosystems and to use the map as a tool to assess local ecosystems' resilience to change and to mitigate adverse anthropogenic effects. We also identified factors which are fast eroding the ecological integrity of the study area: human encroachment (urban expansion, fragmentation, etc.), sand quarries, overgrazing, hydrological changes, fires and pollution. We noted that while soil erosion is increasing at low at medium altitudes, wind erosion is gradually silting up the area, including dunary marshes and ponds, thus limiting the carrying capacity of habitats and reducing their biodiversity. The draining of marshes is altering their hydrological functions and is inducing the loss of indigenous and hygrophilous plants, replaced by pyrophilous ones. The dam, located upstream of the study area, is also increasing water pollution by reducing the water flow.In order to stem the increasing erosion of local biodiversity and sustain wetlands resilience (K.L. ERWIN, 2009), steps are urgently needed to provide capacity building to local managers, increase connectivity, maintain hydrology, reduce pollution and control invasive species. The phytoecologic diagnostic associated to vegetation and land use maps can be of tremendous help to the management of the area, its conservation and to the sustainable use of its natural resources in the context of global changes.